2016
DOI: 10.1111/cyt.12405
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular proliferation of brain metastases mimics glioblastomas in squash cytology

Abstract: The vascular features of metastatic brain tumours are similar to those of glioblastomas, suggesting that these microvascular proliferations contribute to the progression of metastatic tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…6a ). This was of interest given the relationship between microvascular proliferation and high-grade glioma 35 , potentially suggesting localized cellular niches of more aggressive tumour features within metastases. Endothelial cell proliferation appeared to be suppressed via interactions with CD8 + T cells—an effect that was specific to BrM-cores (Fig.…”
Section: Single-cell Interaction Networkmentioning
confidence: 99%
“…6a ). This was of interest given the relationship between microvascular proliferation and high-grade glioma 35 , potentially suggesting localized cellular niches of more aggressive tumour features within metastases. Endothelial cell proliferation appeared to be suppressed via interactions with CD8 + T cells—an effect that was specific to BrM-cores (Fig.…”
Section: Single-cell Interaction Networkmentioning
confidence: 99%
“…Our results showed that tumor microvasculature of MLC had significantly larger microvessel diameters compared to PCNSLs, whereas microvessel size did not significantly differ between MLC tumors and GBMs nor between PCNSLs and GBMs. A histopathological study by Gi et al demonstrated that metastatic brain tumors, similar K to high-grade gliomas, are characterized by a large, thick, dilated glomeruloid microvasculature compared to normal brain tissue or malignant lymphomas [26], which could explain the non-significant difference in the mean vessel diameters between GBMs and MLCs. The lack of statistical significance in the comparison of microvessel size and density between GMBs and PCNSLs could be attributed to the small sample size but partially also to the fact that GBMs seem to alter their microvasculature as they evolve, with smaller tumors presenting with smaller vessels more similar to PCNSLs (which are less vascular and exhibit a characteristic angiocentric pattern in which tumor cells accumulate densely within and around blood vessels [27]).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour angiogenesis has been revealed to be involved in mediating tumour growth and metastasis . The high level of microvessel density can be identified as an independent prognostic indictor for glioma patients . Ma et al identified SNHG15 as a novel lncRNA involved in the growth of glioma microvascular endothelial cells .…”
Section: Expression Pattern Functions and Clinical Potentials Of Snhmentioning
confidence: 99%
“…102,103 The high level of microvessel density can be identified as an independent prognostic indictor for glioma patients. 104,105 Ma et al identified SNHG15 as a novel lncRNA involved in the growth of glioma microvascular endothelial cells. 106 Their study demonstrated that SNHG15 was significantly increased in glioma-mediated human cerebral microvascular endothelial cells (hCMECs), which was cultured in the glioma conditioned medium (GCM) to simulate the glioma microenvironment.…”
Section: Gliomamentioning
confidence: 99%